2015
DOI: 10.4274/tjo.67878
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Visual Acuity on the Surgical Outcomes of Secondary Sensory Strabismus

Abstract: Objectives:To investigate the outcomes of secondary sensory strabismus surgery and to discuss the effect of visual acuity on success.Materials and Methods:The medical records of patients with sensory strabismus who underwent recession-resection on the eye with vision loss were reviewed. Only patients with visual acuity of ≤0.2 in the operated eye were enrolled. Data including age at surgery, visual acuity, etiology of vision loss, preoperative and postoperative deviations, follow-up duration, and surgical outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 21 publications
1
11
1
Order By: Relevance
“…In this study, 62.5% of patients with sensory exotropia had a successful outcome, with an average of 2.0 ± 1.2 years of follow-up. This result is comparable to those reported in other studies on sensory strabismus surgery, although the inclusion criteria and the length of follow-up vary widely among reports [4][5][6]12].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In this study, 62.5% of patients with sensory exotropia had a successful outcome, with an average of 2.0 ± 1.2 years of follow-up. This result is comparable to those reported in other studies on sensory strabismus surgery, although the inclusion criteria and the length of follow-up vary widely among reports [4][5][6]12].…”
Section: Discussionsupporting
confidence: 88%
“…Gusek-Schneider et al reported that surgical success in sensory exotropia was correlated with visual acuity in a total 19 patients [8]. Finally, Turan et al reported that better visual acuity may predict better outcome in terms of long-term success in patients with sensory exotropia [4]. However, there were no significant factors associated with surgical outcome in our study.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…A lateral rectus recession exceeding 7.0 mm to 8.0 mm behind the equator is also said to reduce abduction significantly [ 28 , 30 ] and causes limitation of ocular rotation [ 31 , 32 ]. Several previous studies of large-angle exotropia have reported success rates ranging from 72 to 80% in bilateral lateral rectus recessions, without significant abduction limitations [ 32 ].…”
Section: Discussionmentioning
confidence: 99%